Bored and spoiling for a flight: capabilities lost and found in lockdown - Sommer, Doris (Frontiers in Sociology, 2023)
Human beings are dynamic; our innate faculties beg to engage in activities. To achieve fullness and human dignity, people "convert" personal capabilities into active "functionings," Amartya Sen explains. This means that staying still is not a normal state. It can feel like punishment. Forced inactivity will generate resentment, resistance, and boredom that can fester until pent-up energy explodes violently, or implodes in depression. Boredom defaults on capabilities and resources in many cases. In other cases, stillness is a gift. It can stimulate the imagination to fill in emptiness with memories and new explorations. Either boredom builds toward doing damage, or it releases energy to think and to create. What people don't do is stay put, mentally or physically. Authorities -including police, judges, teachers, parents –should take this dynamic human condition into account and reconsider the effects of conventional command and control policies. Then they can choose between violence and creativity as alternative outlets for the energy that boredom generates. Short of facing up to human dynamism, decision-making may continue to favor strong-arm tactics, which trigger the violence and pain that policing is meant to mitigate. Is it surprising that apparently peaceful people become enraged in lockdown conditions? Do adults wonder why students drop-out of school and suffer escalating rates of depression and suicide? Boredom is certainly not the only cause for these disastrous effects, but to ignore it risks remaining complicit with processes that perpetuate personal and collective dysfunctions. Complicity with harmful practices will miss opportunities to channel frustrated energy toward developing human capabilities. Authorities are responsible for promoting peaceful development. We are all responsible.[2]Normally, people stay busy with routine activities. We work, play, attend to family and to friends. Particular activities have even become our public badges of identity, as is evident in surnames (Cooper, Baker, Taylor, Farmer, etc.) that trace back to work that ancestors answered to. Lockdown during Covid-19 meant that many otherwise occupied people had few outlets for energy. Those who knew how to meditate managed to assuage anxiety through contemplation and the pursuit of ideal emptiness.